Human SLC26A1 Gene Variants: A Pilot Study - Paul A. Dawson; Pearl Sim; David W. Mudge; David Cowley (The Scientific World Journal)
Kidney stones are a global health problem, incurring massive health costs annually. Why stones recur in many patients remains unknown but likely involves environmental, physiological, and genetic factors. The solute linked carrier (SLC) 26A1 gene has previously been linked to kidney stones in mice. SLC26A1 encodes the sulfate anion transporter 1 (SAT1) protein, and its loss in mice leads to hyperoxaluria and calcium oxalate renal stones. To investigate the possible involvement of SAT1 in human urolithiasis, we screened the SLC26A1 gene in a cohort of 13 individuals with recurrent calcium oxalate urolithiasis, which is the commonest type. DNA sequence analyses showed missense mutations in seven patients: one individual was heterozygous R372H; 4 individuals were heterozygous Q556R; one patient was homozygous Q556R; and one patient with severe nephrocalcinosis (requiring nephrectomy) was homozygous Q556R and heterozygous M132T. The M132 amino acid in human SAT1 is conserved with 15 other species and is located within the third transmembrane domain of the predicted SAT1 protein structure, suggesting that this amino acid may be important for SAT1 function. These initial findings demonstrate genetic variants in SLC26A1 of recurrent stone formers and warrant wider independent studies of SLC26A1 in humans with recurrent calcium oxalate stones.